Slovenščina na dlani 2 (University of Maribor Press, 2019)
Slovene in the Palm of Your Hand 2. The monograph is a continuation of the publication Slovene in the Palm of Your Hand 1. In the first part, the results of the project Slovene in the Palm of Your Hand, which is being carried out at the University of Maribor from 2017 until 2021, are presented. It outlines the e-environment for learning from the perspective of the teacher’s and the pupil’s user experience. As the e-environment provides exercises in orthography, grammar, phraseology, and texts, exercises can be prepared considering both the curricula and the process of automation. The area of phraseology will also include a dictionary description of selected units. Therefore, the 100 idioms and the 100 proverbs that were selected for a more detailed analysis are presented. The monograph also elaborates the knowledge that pupils will gain through the collection of texts, called BERTA. The second part provides papers by Slovene language teachers. Drawing upon their experience in working with pupils and high school students, they introduce original ideas for teaching grammar, lexicology, phraseology, and text types while highlighting effective teaching methods which inspired pupils and high school students to learn and research the Slovene language. The papers show that all subject matters, can be presented as challenges and therefore encourage learners to be more creative and search for alternative solutions.